Identifikasi Struktur Organ Vegetatif Tumbuhan Sesajen Hari Raya Waisak Maha Vihara Majapahit - Fikriah, Lailatul; Ami, Mucharommah Sartika (Exact Papers in Compilation (EPiC), 2022)
This study aims to identify the plant species and the morphological structure of the vegetative organs of plants used in offerings for Vesak Day at Maha Vihara Majapahit. The approach used in this research is descriptive. The vegetative organs whose morphological structures were identified were only the vegetative organs used as offerings. The reference used in identifying the morphological structure of vegetative organs is the book Plant Morphology by Gembong Tjitrosoepomo. The data obtained were then analyzed descriptively qualitatively. The results of the identification showed that there were 13 plant species whose vegetative organs were utilized in the Vesak Day offerings at Maha Vihara Majapahit. The vegetative organs used are the leaves. 11 species were single leaf plants and 2 species were compound leaf plants. A total of 9 species had a pinnate leaf spine type, 2 plants were parallel type, and 1 plant was curved type.